Presentation of conjunctival amyloidosis as bilateral ptosis and cicatricial entropion - Kumar Sambhav (Saudi Journal of Medicine and Medical Sciences, 2013)
Primary localized amyloidosis of the conjunctiva is a rare occurrence. This case report describes a 35-year-old male, who presented with drooping of both upper eyelids and a pricking sensation in the left eye. Examination of the conjunctiva showed granular swellings. The biopsy revealed amyloid deposition. Systemic amyloidosis was ruled out on further investigation. To our knowledge, this is the first report of amyloidosis of the conjunctiva and tarsus, presenting as ptosis with entropion, from India.